2011
DOI: 10.1021/bc100403e
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer Display of Tumor-Homing Peptides

Abstract: In vivo selection of phage libraries that display random peptide sequences on their surface has yielded a number of peptides that specifically home to tumor tissue. In this study, two different peptides are introduced to synthetic dendritic scaffolds via oxime chemistry and the resulting compounds are analyzed for tumor homing. Modification of the dendritic wedge with a short, linear peptide that homes to clotted plasma proteins showed that a specific receptor in tumor tissue is recognized, but that the extrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…[37] Meijer and co-workers have used the oxime ligation to tether tumor-homing peptides onto a dendrimer. [38] These representative examples show that performing simultaneously multiple oxime ligations is a convenient access to multivalent compounds.…”
Section: The Oxime Ligation: a Chemical Tool For Bioconjugate Assembliesmentioning
confidence: 99%
“…[37] Meijer and co-workers have used the oxime ligation to tether tumor-homing peptides onto a dendrimer. [38] These representative examples show that performing simultaneously multiple oxime ligations is a convenient access to multivalent compounds.…”
Section: The Oxime Ligation: a Chemical Tool For Bioconjugate Assembliesmentioning
confidence: 99%
“…[229] Ein Vorteil von Dendrimeren ist die Mçglichkeit, sie mit verschiedenen chemischen Einheiten zu dekorieren. [232] Der Kern, Lyp-1, enthält ein cyclisches Nonapeptid, das spezifisch in lymphatischen Zellen und Makrophagen vorkommt, und CREKA, ein gegen Tu moren gerichtetes,lineares Peptid, das an den Fibrin-Fibronektin-Komplex in der extrazellulären Matrix des Tu mormikroumfelds bindet. B. gegen Peptide gerichtete Motive,w urden kovalent an Dendrimere gebunden, um peptiddekorierte Dendrimere (PDDs) zu erhalten, [230] besonders fürdie Ausrichtung auf Tumoren.…”
Section: Multimere Liganden Als Proteinkomplexmimetika Oder Zur Proteunclassified
“…The N-terminus of a protein or alternatively, orthogonally protected lysines can be used for site-specific ketone incorporation. For this purpose, pyruvic acid and levulinic acid have been used [1,2,11,14,55]. However, the choice of ketone is not arbitrary; we found that levulinic acid is prone to an intramolecular cyclization reaction [56].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Oxime ligation has gained considerable attention over the past decade and is being used for a large number of applications, mainly in the field of bioconjugation. Examples include synthetic proteins [1][2][3][4][5][6], bioconjugates [7][8][9][10][11] and multivalent constructs [3,[12][13][14]. An oxime bond is the result of a condensation reaction of a ketone or aldehyde and an aminooxy moiety to result in a ketoxime or aldoxime, respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%